A HYBRID RECOGNITION METHOD THROUGH VIDEO SURVEILLANCE USING COMBINED HARRIS-EDGE - Indrabulan, Tantri (Department of Electrical Engineering, University of Patria Artha, 2018)
This paper discuss Intelligent Transportation System (ITS) which is incorporated with computer vision techniques in recognition of vehicles for typical fast growth cities in development countries. Two algorithm are combined i.e. Harris and Edge Prewitt to increase accuration of vehiclesâ detection. Verification is conducted using Support Vector Machine (SVM) and Histograms of Oriented Gradiens (HOG) as its descriptor. Six pieces of experimental videos from a wide variety of road conditions are used for processing. It shows thatÂ percentage average for sensitivity is 75.73%, specificity 90.1% precision 56.0% and with accuration of 77.73%.